PERANCANGAN SISTEM ADMINISTRASI PEMBAGIAN JASA TENAGA KESEHATAN RS TNI AU DR. DODY SARJOTO - Tadius, Alhentho Reynoldy (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2019)
This research was conducted at the Indonesian Air Force Hospital dr. Dody Sarjoto Makassar. Like government and private hospitals in general, the Air Force Hospital dr. Dody Sarjoto Makassar also implements a system of distribution of Health Personnel Services (JTK) or to the Government Hospital commonly known as Remuneration for Medical Services. The division of JTK is an important thing to consider, because it is related to the welfare of medical staff and paramedics. The purpose of this research is to design a web-based system that can manage patient service data and help the hospital in calculating the JTK division. The method used in designing this system is the SDLC Waterfall method. The result of this system is that it can assist the cashier and treasurer in managing the patient service data of the General Community and optimize the time in the process of making the JTK division.Keywords: Administration, Distribution of Health Services, JTK Distribution Hospital, Remuneration